PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA MUHAMMADIYAH 2 PONTIANAK - Nor Ikmal; Sulistyarini Sulistyarini; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was motivated by the demands of the 2013 curriculum where students are required to be able to think critically, so that a learning model was needed that can improve students' critical thinking skills. This study aims to determine the effect of applying the Problem Based Learning model to critical thinking skills of class XI IIS 2 Muhammadiyah Senior High School Pontianak. This research was conducted with a quantitative approach and a quasi experimental design method with the form of Pretest-Posttest Control Group Design and the sample in this study was a class XI IIS student of Muhammadiyah 2 High School Pontianak. The results of prettest and posttets analysis of data on sociology subjects in class XI IIS of Muhammadiyah 2 High School in Pontianak showed that 1) the Gain calculation results obtained increased by 16.53 points, between the matter of the pretest and Posttest. 2) the average result of the posttest question of the first meeting is 64.20 and the second meeting is 74.67. 3) the results of the percentage of completeness of students in working on the problem of the first posttest meeting 73% with 22 students completing from 30 students and the second meeting amounting to 90% with 27 students completed from 30 students. 4) the results of the Wilcoxon first meeting with a significance value of 0,000 and the second meeting with a significance value of 0,000, with a significance level of 0.05. Keywords: Problem Based Learning Model, Thinking Ability Critical